Adaptations for rehabilitation services during the COVID-19 pandemic proposed by scientific organizations and rehabilitation professionals - Luz H. Lugo-Agudelo; Kelly Mariana Cruz Sarmiento; Maria Alejandra Spir Brunal; Juan Carlos Velásquez Correa; Ana Maria Posada Borrero; Luisa Fernanda Mesa Franco; Rosarita Di Dio Castagna Ianini; Paola Andrea Ramírez Pérez Lis; Claudia Marcela Vélez; Daniel F. Patiño Lugo; Christoph Gutenbrunner (Medical Journals Sweden, 2021)
Objective: To describe adaptations in the provision of rehabilitation services proposed by scientific and professional rehabilitation organizations to avoid interruptions to patients rehabilitation process and delays in starting rehabilitation in patients with COVID-19. Methods: A narrative review approach was used to identify the recommendations of scientific and professional organizations in the area of rehabilitation. A systematic search was performed in the main data-bases in 78 international and regional web portals of rehabilitation organizations. A total of 21 publications from these organizations were identified and selected. Results: The results are presented in 4 categories: adequacy of inpatient services, including acute care services and intensive care unit for patients with and without COVID-19; adequacy of outpatient services, including home-based rehabilitation and tele-rehabilitation; recommendations to prevent the spread of COVID-19; and regulatory standards and positions during the COVID-19 pandemic expressed by organizations for protecting the rights of health workers and patients. Conclusion: Health systems around the world are rapidly learning from actions aimed at the reorganization of rehabilitation services for patients who are in the process of recovery from acute or chronic conditions, and the rapid response to the rehabilitation of survivors of COVID-19, as well as from efforts in the prevention of contagion of those providing the services.